Management of Ankle Fractures with Syndesmotic Disruption: A Survey of Orthopaedic Surgeons. Issue 4 (22nd October 2020) - Rogero, Ryan G.; Illical, Emmanuel M.; Corr, Daniel; Raikin, Steven M.; Krieg, James; Tsai, Justin
Category: Ankle; Trauma Introduction/Purpose: With an increasing frequency of syndesmotic fixation during ankle fracture ORIF and no current gold standard management protocol, it is important for surgeons to understand the frequency and usage patterns of the various techniques among other orthopaedic surgeons. The purposes of this study are to determine how orthopaedic surgeons currently manage ankle fractures with concomitant syndesmotic disruption and to identify surgeon demographics predictive of syndesmotic management. Methods: An 18-question survey, including 10 specific syndesmotic management questions was sent to the Orthopaedic Trauma Association (OTA) and Canadian Orthopaedic Association (COA), as well as sent to email addresses of foot and ankle-fellowship trained surgeons. Surgeon demographic questions included years, country, and type of practice, fellowship(s) completed, setting of ankle fracture surgery, and number of ankle fractures operated on per year. Multinomial regression analysis was performed to determine if surgeon demographics were predictive of syndesmotic management. Results: One-hundred ten orthopaedic surgeons completed our survey. Selected predictors of syndesmotic management included: private practice with academic appointments (0.077 [0.007, 0.834]; p=0.035) being predictive of not using screws through an ORIF plate; foot & ankle fellowship (9.981 [1.787, 55.764]; p=0.009) and trauma fellowship (6.644 [1.302, 33.916]; p=0.023) predictive of utilizing screws through a plate; no fellowship (14.886 [1.226, 180.695]; p=0.034) predictive of only using 1 screw; and surgeons practicing in the U.S. were more likely to not use screws across just 3 cortices (0.031 [0.810, 3.660]; p=0.009). Additionally, among those utilizing suture-button devices, foot & ankle fellowship-trained surgeons were more likely to implement suture-button through plate (7.676 [1.286, 45.806]; p=0.025). Conclusion: Several surgeon factors influence decision making in the management of ankle fractures with syndesmotic disruption. This study raises awareness of differences in management strategies that should be used for further discussion when determining a potential gold standard for management of these complex injuries.